2008
DOI: 10.1016/j.pain.2008.03.019
|View full text |Cite
|
Sign up to set email alerts
|

EphrinB-EphB receptor signaling contributes to neuropathic pain by regulating neural excitability and spinal synaptic plasticity in rats

Abstract: Bidirectional signaling between ephrins and Eph receptor tyrosine kinases was first found to play important roles during development, but recently has been implicated in synaptic plasticity and pain processing in the matured nervous system. We show that ephrinB-EphB receptor signaling plays a critical role is induction and maintenance of neuropathic pain by regulating neural excitability and synaptic plasticity in the dorsal root ganglion (DRG) and the spinal dorsal horn (DH). Intrathecal application of blocki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(131 citation statements)
references
References 51 publications
12
118
1
Order By: Relevance
“…WNT agonist-induced thermal and mechanical hypersensitivity, the values represent the mean of both feet of the rat. The protocols used for determining the pain-related behaviors are similar to those we have previously described (38,49,50).…”
Section: Methodsmentioning
confidence: 99%
“…WNT agonist-induced thermal and mechanical hypersensitivity, the values represent the mean of both feet of the rat. The protocols used for determining the pain-related behaviors are similar to those we have previously described (38,49,50).…”
Section: Methodsmentioning
confidence: 99%
“…Intrathecal administration of ephrinB2-Fc chimera to Wistar rats induced behavioral evidence of thermal hyperalgesia (35). Conversely, pharmacological antagonization of EphB1 prevented nerve injury-induced dorsal horn neuron hyperexcitability and neuropathic pain (37). Not only in somatic pain caused by injury or inflammation, our study investigating cross talk between pelvic viscera has demonstrated that acute activation of transient receptor potential vanilloid 1 expressing nociceptive afferent fibers coming from the descending colon upregulated spinal ephrinB2 expression and simultaneously induced EphB1/2 phosphorylation in the lumbosacral dorsal horn (28).…”
Section: F408mentioning
confidence: 98%
“…Following nerve injury, the expression of ephrinB2 in dorsal root ganglion (DRG) neurons and the EphB1 receptor in the dorsal horn were both enhanced in a time-dependent manner corresponding to the development of thermal hyperalgesia in adult rats (36,37). Knock-down of ephrinB2 using specific short interfering RNA decreased expression of ephrinB2 in the DRG, along with attenuation of mechanical allodynia caused by spinal nerve crushing (13).…”
Section: F408mentioning
confidence: 99%
“…However, the ephrin-B-EphB receptor signalling has been shown to contribute to neuropathic pain by regulating excitability of nociceptive-related neurons in dorsal root ganglion and dorsa horn and the synaptic plasticity at the spinal level (15). Moreover, ephrin-B2 siRNA may be a potential therapeutic agent for neuropathic pain (16).…”
Section: -B2 --------------------------------------------------------mentioning
confidence: 99%